2020
DOI: 10.1051/0004-6361/202038057
|View full text |Cite
|
Sign up to set email alerts
|

High-speed stars: Galactic hitchhikers

Abstract: Context. The search for stars born in the very early stages of the Milky Way star formation history is of paramount importance in the study of the early Universe since their chemistry carries irreplaceable information on the conditions in which early star formation and galaxy buildup took place. The search for these objects has generally taken the form of expensive surveys for faint extremely metal-poor stars, the most obvious but not the only candidates to a very early formation. Aims. Thanks to Gaia DR2 radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 101 publications
0
4
0
Order By: Relevance
“…Gaia DR-2 has provided radial velocity information about 7 million stars (Katz et al 2019). A number of studies have already combed through this sample to unearth evidence for hypervelocity stars (Bromley et al 2018;Hattori et al 2018;Du et al 2019;Marchetti et al 2019;Boubert et al 2019;Caffau et al 2020;Li et al 2020). To the best of our knowledge, the fastest hypervelocity star from any survey is S5-HVS1 from the Southern Stellar Stream Spectroscopic Survey with a velocity of ∼ 6 × 10 −3 c (Koposov et al 2020), while HVS 22 from the Multiple Mirror Telescope survey exhibits a similar velocity of ∼ 5×10 −3 c (Kreuzer et al 2020).…”
Section: Constraints On Stellar Enginesmentioning
confidence: 99%
“…Gaia DR-2 has provided radial velocity information about 7 million stars (Katz et al 2019). A number of studies have already combed through this sample to unearth evidence for hypervelocity stars (Bromley et al 2018;Hattori et al 2018;Du et al 2019;Marchetti et al 2019;Boubert et al 2019;Caffau et al 2020;Li et al 2020). To the best of our knowledge, the fastest hypervelocity star from any survey is S5-HVS1 from the Southern Stellar Stream Spectroscopic Survey with a velocity of ∼ 6 × 10 −3 c (Koposov et al 2020), while HVS 22 from the Multiple Mirror Telescope survey exhibits a similar velocity of ∼ 5×10 −3 c (Kreuzer et al 2020).…”
Section: Constraints On Stellar Enginesmentioning
confidence: 99%
“…Du et al (2018Du et al ( , 2019 use Gaia and LAMOST data to discover that some high-velocity stars origin from the tidal debris of disrupted dwarf galaxies. Caffau et al (2020) used the Gaia DR2 and VLT data to present the chemodynamical investigation of a 72 high-velocity sample stars and suggested that these stars can be the result of a disrupted small galaxy or globular cluster members. Marchetti (2021) derived that 7 high-velocity stars possibly origin from an extragalactic origin from Gaia EDR 3.…”
Section: Introductionmentioning
confidence: 99%
“…The availability of accurate parallaxes, proper motions, and for the brightest stars also radial velocities has revived this kind of selection. Our group has been using FORS at the VLT to explore the chemical properties of stars with transverse velocities in excess of 500 km s −1 (Caffau et al, 2020). This allowed to select stars with extreme kinematics, including five formally unbound stars, more than half of the sample turned out to be on retrograde orbits.…”
Section: Introductionmentioning
confidence: 99%